THE ART OF LITERARY TRANSLATION: NAVIGATING STYLISTIC DEVICES (Web of Teachers: Inderscience Research, 2025)
Literary translation is a complex process that goes beyond the simple transfer of meaning from one language to another. It involves the intricate task of recreating the artistic and aesthetic effects of the original text, which are often conveyed through the use of stylistic devices. This article explores the challenges and strategies involved in translating these devices, examining their role in shaping the reader's experience and the importance of the translator's interpretive and creative skills.